Status of retraction notices for biomedical publications associated with research misconduct. (April 2019) - Drimer-Batca, Daniel; Iaccarino, Jonathan M; Fine, Alan
In order to assess the status of retraction notices for publications involving research misconduct, we collected and analyzed information from the Office of Research Integrity website. This site lists confirmed instances of misconduct in research supported by the National Institutes of Health. Over a 10-year period, 200 publications derived from misconduct were identified. For 20.5% of those papers, no retraction notice was published. We found that the majority of these cases were from investigations concluded at least two years before our analysis, and thus are unlikely to be explainable by timing considerations. These findings demonstrate that retraction notices for papers associated with misconduct are often not published and suggest that clear, adherent policies are needed in this circumstance to correct the scientific record.